Factor influencing the perception of customer toward Islamic banking: A case study in Alor Gajah, Melaka / Amirul Irfan Wisam - Wisam, Amirul Irfan (Academy of Contemporary Islamic Studies, 2018)
The banking system not success due to certain factors like awareness regarding Islamic banking system when the Islamic banking was start in 1963 in Malaysia. Then new Islamic bank Dubai Islamic bank was established in 1975. Today approximately 100 banks are operating without interest, but the market of Islamic banking system is low as compared to conventional banking system. The reasons of this research are to check the impact of knowledge and awareness, online banking, advertising and service quality on the perception of customers toward Islamic banking system in Alor Gajah. For this purpose, survey is used which consist of 88 Muslims respondent in different Islamic bank in Alor Gajah, Melaka. Result of this study indicates that there is a significant perception criterion regarding Islamic banking system (IBS). The data is analysed by using SPSS software version. Mostly respondent know about the Islamic banking product and service but they are not used these product and service. This study indicates that there is need to educate the people about IBS and more work are still required to compete with conventional banking system in Malaysia.